Growth in two deep-sea associates: the octocoral Pseudogorgia bellona and the euryalid snake star Asteroschema ajax - Cook, Isobel; Okanishi, Masanori; Pante, Eric (Zootaxa, 2023)
The deep-sea octocoral Pseudochrysogorgia bellona was recently described from specimens sampled on the Chesterfield Plateau, off New Caledonia. It is morphologically and genetically similar to the con-familial Metallogorgia melanotrichos, which is known to closely associate with a species of brittle star, Ophiocreas oedipus. These latter two species have never been observed separately and are thought to grow synchronously. The morphological similarity between M. melanotrichos and P. bellona makes the latter another possible host for ophiuroids. However, no brittle star was associated with P. bellona specimens from the type collection. In 2017, 130 P. bellona colonies were sampled near the type locality, and 98% were associated with Asteroschema ajax, a species closely related to O. oedipus. Mitochondrial DNA analysis confirmed the morphological identifications of both P. bellona and A. ajax. Uni- and multivariate statistical analyses were used to characterize the morphological space of both species to test if larger ophiuroids are associated with larger corals. Two variables were measured to estimate the size of the coral (total height and diameter of the skeletal axis at its base) and 9 variables were used to characterize the brittle star (disc and arm morphology). Morphological variables representing the size for both species were significantly correlated (Spearman rank correlation coefficient: 50%, p < 0.001), suggesting that larger ophiuroids indeed associate with larger corals. This is one of the rare studies that allowed comparison of growth in associated deep-sea invertebrates.